Penyuluhan Tentang Covid -19 Dan Diabetes Mellitus Di Dusun Taeno Desa Rumah Tiga - Abd. Rijali Lapodi; Herlien Sinay; Suryanti Tukiman (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2023)
Diabetes Mellitus (DM) is a metabolic disorder characterized by increased blood sugar levels due to insufficient insulin function. Patients with diabetes mellitus often experience other health problems such as obesity, heart disease and kidney disease which further exacerbate their health problems, especially if they are exposed to Covid 19 which can eventually lead to death. The need for information that strengthens and refreshes the knowledge possessed is urgently needed so that while living life during this pandemic, you can stay healthy. The method used in community service activities is carried out by counseling and discussion methods. This activity was carried out face-to-face, the total number of activity participants was 45 people, although initially it was targeted to be 100 people. The results of this activity, the people of Taeno Hamlet said that 80% felt very satisfied and 20% were satisfied with this counseling activity. These results were obtained through a questionnaire after this activity took place. This can be seen by the enthusiasm of the participants to ask about a healthy lifestyle. Patients with diabetes mellitus must have a healthy behavior and exercise diligently in order to maintain body stamina and follow the treatment that has been carried out so far. Counseling activities for patients with co-morbidities not only diabetes mellitus are urgently needed to provide information, strengthen understanding and provide updated information regarding how Covid 19 can affect patients, especially those with comorbidities.